The Semiotics of Solidarity: Reinterpreting Artefacts of Latin American Resistance in Contemporary Leeds (Alternautas, 2024)
This paper examines reinterpretations of solidarity with Latin America through a student-led project at the University of Leeds. The project, ‘Thinking Inside the Box: 1973’ (hereafter, TITB), was a collaboration between the University of London – specifically, King’s College London, Queen Mary University of London, and the London School of Economics – and the Universities of Leeds and Liverpool in 2023. The broader framework of TITB seeks to generate liberatory and transformative learning by approaching the educative process with students as co-creators and co-curators of knowledge. The approach draws from decolonial theory by seeking to challenge the hierarchical practices of mainstream education in which the teacher imposes knowledge on the student. In dialogue with Freirian concepts of collective interpretation and ‘conscientisation’ (Freire, 1968), scholars and students involved in the project used archives to run a series of events and public engagements. It connects students to each other and to a range of archival materials, broadly themed around 20th century Latin America, to inspire them in designing, developing and delivering an output of significant impact by engaging with local communities; in this case, the Chilean diaspora of the dictatorship. The project promotes the co-curation of knowledge, teaching and learning, and supports students to practice autonomy in their journeys of content and skills acquisition (Grimaldi, Carvalho and Natale, 2022; Grimaldi and Rofe, 2023).